(untitled) (e-Journal of Linguistics, 2025)
The song "Takkan Terganti" by Yovi Widianto tells about true love that is irreplaceable, even though it has to face loss and longing. This study aims to analyze the semantic meaning of the song’s lyrics using a qualitative descriptive method with a scalpel of figurative, contextual, metaphorical, symbolism and polysemy analysis approaches. The study shows that each verse of the song uses the scalpel above so that it has various meanings, such as loneliness and eternal love. The function of language is dominated by expressive and aesthetic functions, and polysemy enriches the interpretation of dimensions. In conclusion, this song conveys a message of strong and eternal love, making it a meaningful song.